Application of the European quality indicators for psychosocial dementia care in long-term care facilities in the Asia-Pacific region: a pilot study. (3rd October 2018) - Jeon, Yun-Hee; Chien, Wai Tong; Ha, Ju-Young; Ibrahim, Rahimah; Kirley, Belinda; Tan, Lay Ling; Thaipisuttikul, Papan; Vasse, Emmelyne; Vernooij-Dassen, Myrra; Wang, Huali; Youn, Jong-Chul; Brodaty, Henry
ABSTRACT: Objectives : An Asia-Pacific regional collaboration group conducted its first multi-country research project to determine whether or not European quality indicators (QIs) for psychosocial care in dementia could be implemented as a valid tool in residential aged care across seven Asia-Pacific sites (Australia, Hong Kong Special Administrative Region, Mainland China, Malaysia, Singapore, South Korea, and Thailand). Method : Following the European QI protocol, auditing and data extraction of medical records of consenting residents with dementia were conducted by trained auditors with relevant health care backgrounds. Detailed field notes by the auditors were also obtained to describe the characteristics of the participating care facilities, as well as key issues and challenges encountered, for each of the 12 QIs. Results : Sixteen residential care facilities in the seven Asia-Pacific sites participated in this study. Data from 275 residents' records revealed each of the 12 Qis' endorsement varied widely within and between the study sites (0%–100%). Quality of the medical records, family and cultural differences, definitions and scoring of certain indicators, and time-consuming nature of the QI administration were main concerns for implementation. Conclusion : Several items in the European QIs in the current format were deemed problematic when used to measure the quality of psychosocial care in the residential aged care settings in participating Asia-Pacific countries. We propose refinements of the European QIs for the Asian-Pacific context, taking into account multiple factors identified in this study. Our findings provide crucial insights for future research and implementation of psychosocial dementia care QIs in this region.